Phenotypic divergence among threespine stickleback that differ in nuptial coloration. Issue 6 (18th February 2020) - Jenck, Clara S.; Lehto, Whitley R.; Ketterman, Brian T.; Sloan, Lukas F.; Sexton, Aaron N.; Tinghitella, Robin M.
Abstract: By studying systems in their earliest stages of differentiation, we can learn about the evolutionary forces acting within and among populations and how those forces could contribute to reproductive isolation. Such an understanding would help us to better discern and predict how selection leads to the maintenance of multiple morphs within a species, rather than speciation. The postglacial adaptive radiation of the threespine stickleback ( Gasterosteus aculeatus ) is one of the best‐studied cases of evolutionary diversification and rapid, repeated speciation. Following deglaciation, marine stickleback have continually invaded freshwater habitats across the northern hemisphere and established resident populations that diverged innumerable times from their oceanic ancestors. Independent freshwater colonization events have yielded broadly parallel patterns of morphological differences in freshwater and marine stickleback. However, there is also much phenotypic diversity within and among freshwater populations. We studied a lesser‐known freshwater "species pair" found in southwest Washington, where male stickleback in numerous locations have lost the ancestral red sexual signal and instead develop black nuptial coloration. We measured phenotypic variation in a suite of traits across sites where red and black stickleback do not overlap in distribution and at one site where they historically co‐occurred. We found substantial phenotypic divergence between red and black morphs in noncolor traits including shape and lateral plating, and additionally find evidence that supports the hypothesis of sensory drive as the mechanism responsible for the evolutionary switch in color from red to black. A newly described third "mixed" morph in Connor Creek, Washington, differs in head shape and size from the red and black morphs, and we suggest that their characteristics are most consistent with hybridization between anadromous and freshwater stickleback. These results lay the foundation for future investigation of the underlying genetic basis of this phenotypic divergence as well as the evolutionary processes that may drive, maintain, or limit divergence among morphs. Abstract : Unveiling when or how traits are selected for or against is key to understanding the patterns of phenotypic variation observed in natural populations, especially when multiple morphs are maintained. We measured a comprehensive suite of phenotypic traits in two different freshwater threespine stickleback color morphs, red‐throated and black‐bodied. We found extensive divergence in nuptial color, shape, and body armor between red and black stickleback, and also form a hypothesis for the existence of a possible third, hybrid morph. This is the first in‐depth investigation of variation in morphological traits in populations of red and black stickleback.